2004
DOI: 10.1021/ic035151s
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structures, and Photoluminescence of a Novel Class of d10 Metal Complexes Constructed from Pyridine-3,4-dicarboxylic Acid with Different Coordination Architectures

Abstract: Two novel d(10) metal coordination polymers [Zn(PDB)](n)() (1) and [Cd(3)(PDB)(2)(OH)(2)(H(2)O)(2)](n)() (2) (H(2)PDB = pyridine-3,4-dicarboxylic acid) have been synthesized under hydrothermal conditions and characterized by elemental analysis, IR, TG analysis, and single-crystal X-ray diffraction. Crystal data for 1: C(7)H(3)NO(4)Zn, orthorhombic Pna2(1), a = 8.423(17) A, b = 6.574(13) A, c = 12.899(3) A, Z = 4. Crystal data for 2: C(14)H(12)N(2)O(12)Cd(3), monoclinic C2/c, a= 20.130(4) A, b = 6.692(13) A, c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(101 citation statements)
references
References 39 publications
8
93
0
Order By: Relevance
“…Wasylina et al [28] and Harmon and Shaw [15] have reported the IR spectrum of only one polymorphic form of CA and have given partial vibrational assignments. Several metal complexes of CA have been characterised by IR [7,[29][30][31][32] and Raman [33] spectroscopies. As can be easily seen from Figures 6 and 7, the two polymorphs show significant differences in both IR and Raman spectra for either the presence of some bands only for one polymorph or the wavenumber positions of many bands or their relative intensities.…”
Section: Ir and Raman Measurementsmentioning
confidence: 99%
“…Wasylina et al [28] and Harmon and Shaw [15] have reported the IR spectrum of only one polymorphic form of CA and have given partial vibrational assignments. Several metal complexes of CA have been characterised by IR [7,[29][30][31][32] and Raman [33] spectroscopies. As can be easily seen from Figures 6 and 7, the two polymorphs show significant differences in both IR and Raman spectra for either the presence of some bands only for one polymorph or the wavenumber positions of many bands or their relative intensities.…”
Section: Ir and Raman Measurementsmentioning
confidence: 99%
“…The IR spectrum of 1 shows characteristic bands of carboxyl groups at 1,585 cm -1 for the asymmetric stretching and at 1,392cm -1 for symmetric stretching. The volve of ν(ν as (-COO-)-ν s (-COO-)) indicate that the carboxylate groups coordinate to the metal atoms bridging (Δv value: 193 cm -1 ) fashion [38] . The spectrum also exhibits a strong broad band at 1610 cm -1 indicative of COO as stretching mode, while a peak corresponding to COO s vibration appeared at 1392 cm -1 [34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…The carboxylate groups of ligands act in different modes in metal ion coordination as a bidentate bridging, bidentate chelating, threedentate chelating-bridging or monodentate so the complexes can have different structures either polymeric, dimeric and monomeric. The synthesis and physico-chemical properties of pyridine derivative ligands are important because a diversity of coordinating structures can be formed, including solid coordination polymers and their numerous applications in material chemistry, catalysis, luminescence and magnetochemistry [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%